2017
DOI: 10.1016/j.radonc.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of particle beam therapy and stereotactic body radiotherapy for early stage non-small cell lung cancer: A systematic review and hypothesis-generating meta-analysis

Abstract: Purpose To assess hypo-fractionated particle beam therapy (PBT)'s efficacy relative to that of photon stereotactic body radiotherapy (SBRT) for early stage (ES) non-small cell lung cancer (NSCLC). Methods Eligible studies were identified through extensive searches of the PubMed, Medline, Google-scholar, and Cochrane library databases from 2000 to 2016. Original English publications of ES NSCLC were included. A meta-analysis was performed to compare the survival outcome, toxicity profile, and patterns of fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 129 publications
(157 reference statements)
1
41
0
Order By: Relevance
“…Historically, there have been three main methods for the treatment of cancer: operation, chemotherapy, and radiotherapy. In addition, various meta-analysis studies have evaluated the combination of these methods for typical types of lung cancer (e.g., second malignancies after radiotherapy for prostate cancer [18], chemotherapy in non-small cell lung cancer [19], radiotherapy plus epidermal growth factor receptor tyrosine kinase inhibitors [20], and other treatments [21][22][23][24][25][26]).…”
Section: Additional Results: Evaluation Of Incomplete Clinical Pathwaysmentioning
confidence: 99%
“…Historically, there have been three main methods for the treatment of cancer: operation, chemotherapy, and radiotherapy. In addition, various meta-analysis studies have evaluated the combination of these methods for typical types of lung cancer (e.g., second malignancies after radiotherapy for prostate cancer [18], chemotherapy in non-small cell lung cancer [19], radiotherapy plus epidermal growth factor receptor tyrosine kinase inhibitors [20], and other treatments [21][22][23][24][25][26]).…”
Section: Additional Results: Evaluation Of Incomplete Clinical Pathwaysmentioning
confidence: 99%
“…Among future strategies, expanding use of proton therapy and hadrons (for example, carbon ion) may allow potential dosimetric advantage over photon-based SBRT in reducing dose exposure of critical structures while maintaining target tumor dose coverage. In a recent meta-analysis by Chi et al, a lower incidence of grade ≥3 toxicity was associated with the use of particle therapy (0.9% vs. 3.4%, p = 0.001) [29].…”
Section: Discussionmentioning
confidence: 95%
“…In the pooled analysis, the rate of grade !3 RP was significantly lower for PBT than for SBRT (0.9% [95% CI, 1.1%-3.3%] vs 3.4% [95% CI, 2.9%-4.0%], P < .001), even though tumors that were more advanced in size and T-stage were treated with PBT. 26 A second advantage is that PBT can be used to treat centrally located tumors. Timmerman et al 10 reported that patients with centrally located tumors had a higher rate of grade !3 toxicities and a lower 2-year rate of freedom from severe toxicity (54%), compared with 83% for patients with peripheral tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, their meta-analysis included only preliminary PBT results and had a small sample size. [23][24][25] In a more recent meta-analysis, Chi et al 26 reported that PBT did not improve OS and PFS in comparison with SBRT (P Z .11) based on multivariate analysis, and PBT yielded a better 3year LC (P Z .03); the rate of grade !3 toxicity was lower (4.8% vs 6.9%, P Z .05) based on pooled analysis. Thus, studies with a larger sample size with longer follow-up are required to accurately evaluate PBT in this patient population.…”
Section: Introductionmentioning
confidence: 99%